Impact of Procedure-Related Complications on Long-term Islet Transplantation Outcome. Issue 5 (May 2015) - Caiazzo, Robert; Vantyghem, Marie-Christine; Raverdi, Violeta; Bonner, Caroline; Gmyr, Valery; Defrance, Frederique; Leroy, Clara; Sergent, Geraldine; Hubert, Thomas; Ernst, Oliver; Noel, Christian; Kerr-Conte, Julie; et al.
<x xml:space="preserve">Abstract</x> Background Pancreatic islet transplantation offers a promising biotherapy for the treatment of type 1 diabetes, but this procedure has met significant challenges over the years. One such challenge is to address why primary graft function still remains inconsistent after islet transplantation. Several variables have been shown to affect graft function, but the impact of procedure-related complications on primary and long-term graft functions has not yet been explored. Methods Twenty-six patients with established type 1 diabetes were included in this study. Each patient had two to three intraportal islet infusions to obtain 10, 000 islet equivalent (IEQ)/kg in body weight, equaling a total of 68 islet infusions. Islet transplantation consisted of three sequential fresh islet infusions within 3 months. Islet infusions were performed surgically or under ultrasound guidance, depending on patient morphology, availability of the radiology suite, and patient medical history. Prospective assessment of adverse events was recorded and graded using "Common Terminology Criteria for adverse events in Trials of Adult Pancreatic Islet Transplantation." Results There were no deaths or patients dropouts. Early complications occurred in nine of 68 procedures. β score 1 month after the last graft and optimal graft function (β score ≥7) rate were significantly lower in cases of procedure-related complications (P = 0.02, P = 0.03). Procedure-related complications negatively impacted graft function (P = 0.009) and was an independent predictive factor of long-term graft survival (P = 0.033) in multivariate analysis. Conclusion Complications occurring during radiologic or surgical intraportal islet transplantation significantly impair primary graft function and graft survival regardless of their severity.